2017
DOI: 10.3906/elk-1604-240
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of creepage discharge safety factors against the tangential component of electric fields in the insulation structure of power transformers

Abstract: Abstract:Creepage discharges are a main cause of insulation damage in power transformers during repeated tests or during operation. In this paper, a hazardous region in the insulation structure of power transformers (the interface between solid and liquid insulation at the top edge of a high-voltage electrode) is considered, and the impact of a very important factor of the surface discharge initiation and propagation (the tangential component of the electric field) on the strength of the insulation structure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…4, d presents the length of oil-paper surface in millimeter, the longer the surface length, the less the accompanying insulation strength, it is found that the interface of length d could withstand electric field up to E0. The relationship of insulation stress and surface length is plotted on a logarithmic scale as shown in As the electric field of solid-liquid insulation is analyzed by extensive tests, it is much important to realize that the main life limiting factors of transformer is the reduction of the dielectric strength in the spaces of main insulation [5], conventional wisdom has proposed a solution by adding pressboard between oil-gap to limit the dielectric stress, which is arm to avoid local concentration of high electric field and prevent large gaps inside, the tangential electric stress along the pressboard usually controlled below 1-2kV/mm to minimize the opportunity to initiate creepage discharges [6]. 3There was also investigation about the development of a low permittivity pressboard obtained by blending polymethylpentene fiber with cellulose fiber [7].…”
Section: Introductionmentioning
confidence: 99%
“…4, d presents the length of oil-paper surface in millimeter, the longer the surface length, the less the accompanying insulation strength, it is found that the interface of length d could withstand electric field up to E0. The relationship of insulation stress and surface length is plotted on a logarithmic scale as shown in As the electric field of solid-liquid insulation is analyzed by extensive tests, it is much important to realize that the main life limiting factors of transformer is the reduction of the dielectric strength in the spaces of main insulation [5], conventional wisdom has proposed a solution by adding pressboard between oil-gap to limit the dielectric stress, which is arm to avoid local concentration of high electric field and prevent large gaps inside, the tangential electric stress along the pressboard usually controlled below 1-2kV/mm to minimize the opportunity to initiate creepage discharges [6]. 3There was also investigation about the development of a low permittivity pressboard obtained by blending polymethylpentene fiber with cellulose fiber [7].…”
Section: Introductionmentioning
confidence: 99%